Androgen receptor status is highly conserved during tumor progression of breast cancer. Issue 1 (December 2015) - Grogg, André; Trippel, Mafalda; Pfaltz, Katrin; Lädrach, Claudia; Droeser, Raoul; Cihoric, Nikola; Salhia, Bodour; Zweifel, Martin; Tapia, Coya
Abstract Background With the advent of new and more efficient anti-androgen drugs targeting androgen receptor (AR) in breast cancer (BC) is becoming an increasingly important area of investigation. This would potentially be most useful in triple negative BC (TNBC), where better therapies are still needed. The assessment of AR status is generally performed on the primary tumor even if the tumor has already metastasized. Very little is known regarding discrepancies of AR status during tumor progression. To determine the prevalence of AR positivity, with emphasis on TNBCs, and to investigate AR status during tumor progression, we evaluated a large series of primary BCs and matching metastases and recurrences. Methods AR status was performed on 356 primary BCs, 135 matching metastases, and 12 recurrences using a next-generation Tissue Microarray (ngTMA). A commercially available AR antibody was used to determine AR-status by immunohistochemistry. AR positivity was defined as any nuclear staining in tumor cells ≥1 %. AR expression was correlated with pathological tumor features of the primary tumor. Additionally, the concordance rate of AR expression between the different tumor sites was determined. Results AR status was positive in: 87 % (307/353) of primary tumors, 86.1 % (105/122) of metastases, and in 66.7 % (8/12) of recurrences. TNBC tested positive in 11.4 %, (4/35) of BCs. A discrepant result was seen in 4.3 % (5/117) of primary BC and matching lymph node (LN) metastases. Three AR negative primary BCs were positive in the matching LN metastasis, representing 17.6 % of all negative BCs with lymph node metastases (3/17). Two AR positive primary BCs were negative in the matching LN metastasis, representing 2.0 % of all AR positive BCs with LN metastases (2/100). No discrepancies were seen between primary BC and distant metastases or recurrence (n = 17). Conclusions Most primary (87 %) and metastasized (86.1 %) BCs are AR positive including a significant fraction of TNBCs (11.4 %). Further, AR status is highly conserved during tumor progression and a change only occurs in a small fraction (4.1 %). Our study supports the notion that targeting AR could be effective for many BC patients and that re-testing of AR status in formerly negative or mixed type BC's is recommended.